Puf Mediates Translation Repression of Transmission-Blocking Vaccine Candidates in Malaria Parasites - Jun Miao; Qi Fan; Daniel M. Parker; Xiaolian Li; Jianyong Li; Liwang Cui (2013)
Translational control of gene expression plays an essential role in development. In malaria parasites, translational regulation is critical during the development of specialized transition stages between the vertebrate host and mosquito vector. Here we show that a Pumilio/FBF (Puf) family RNA-binding protein, PfPuf2, is required for the translation repression of a number of transcripts in gametocytes including two genes encoding the transmission-blocking vaccine candidates Pfs25 and Pfs28. Whereas studies to date support a paradigm of Puf-mediated translation regulation through 3′ untranslated regions (UTRs) of target mRNAs, this study, for the first time, identifies a functional Puf-binding element (PBE) in the 5′UTR of pfs25. We provide both in vitro and in vivo evidence to demonstrate that PfPuf2 binds to the PBEs in pfs25 and pfs28 to mediate translation repression. This finding provides a renewed view of Pufs as versatile translation regulators and sheds light on their functions in the development of lower branches of eukaryotes.